Art therapy: beading fun and accessible as art inclusive for children with special needs [Art therapy: meronce asik dan nyaman sebagai inklusi seni untuk anak berkebutuhan khusus] - Rusli, Herman; Miranda, Nadhira; Safitri, Nadia; Yahya, Munawwarah; Zhafira, Nanda; Nayutisa, N (Universitas Syiah Kuala, 2025)
The